Fotografie nieistniejącego świata. O polskiej sztuce fantastycznej - Grodecka, Aneta (Poznańskie Studia Polonistyczne. Seria Literacka, 2017)
Starting with a reconstruction of the views of philosophers and aesthetes on the topic of fantastic images, the Author aims to characterize fantasy art. She describes the reception of this art in Poland, characterizes its determinants, and defines the trend, indicating the most important examples of artistic works. While exploring this approach, she refers to Waldemar Okoń, Jerzy Malinowski, Tomasz Gryglewicz, and Antoni Smuszkiewicz. The convention of fantasy art appears to be a vital, developmental quality, an expression of the rebellion of consciousness against simplifications.